Brain microvascular endothelial cells possess a second cilium that arises from the daughter centriole - Thirugnanam, Karthikeyan; Gupta, Ankan; Nunez, Francisco; Prabhudesai, Shubhangi; Pan, Amy Y.; Nauli, Surya M.; Ramchandran, Ramani (Frontiers in Molecular Biosciences, 2023)
Primary cilia from the brain microvascular endothelial cells (ECs) are specialized cell-surface organelles involved in mediating sensory perception, cell signaling, and vascular stability. Immunofluorescence (IF) analysis of human primary brain microvascular ECs reveals two cilia per cell. To confirm the in vitro observation of the two-cilia phenotype in human primary brain ECs, ECs isolated from mouse brain were cultured and stained for cilium. Indeed, brain ECs from a ciliopathic mouse (polycystic kidney disease or Pkd2−/−) also possess more than one cilium. Primary cilium emerges from the mother centriole. Centriole analysis by IF suggests that in brain ECs, markers for the mother and daughter centrioles stain both cilia, suggesting that the second cilium in brain ECs arises from the daughter centriole. Further quantification of cilia size in brain ECs revealed that cilia arising from the mother centriole are bigger in size compared with cilia from the daughter centriole. Cell cycle analyses using immunoblotting and flow cytometry suggest that the ciliary proteins ARL13B and IFT88 involved in brain EC ciliogenesis are highly expressed only in the G0/G1 and S phases of the cell cycle. The IF analyses of cells arrested at different cell cycle stages indicate that the two-cilia phenotype is highly specific to the G0/G1 phase. Our findings suggest that in addition to the mother centriole, the daughter centriole also plays a role in ciliogenesis in primary cultured ECs.